Sociabilidade e cidadania: os espaços públicos de Salvador como entrelaçamento do concreto, do simbólico e do imaginário - Cíntia San Martin Fernandes (Ciências Sociais Unisinos)
The article discusses the paradigm of sensitive reason as a socio-anthropological tool for the understanding of the social relations taking place in contemporary cities. For this purpose, the author chose Salvador, in the state of Bahia, Brazil, as a constitutive example of a city that builds its sociability, its daily interlacement, not on instrumental rational relationships (ruled by objective and regulating ends and means), but on sensitive reason (ruled by sensitivities, such as art, aesthetics, the body and gestures). The article is divided in three parts: the first one briefly presents some approaches of the concept of network in order to situate the authors perspective among others; the second one elaborates on this approach; the third part describes elements of the nagô [which some call Yoruban] communication, which is seen as a foundation for the interpersonal communication that prevails in the city of Salvador.